Tissue-Specific Floral Transcriptome Analysis of the Sexually Deceptive Orchid Chiloglottis trapeziformis Provides Insights into the Biosynthesis and Regulation of Its Unique UV-B Dependent Floral Volatile, Chiloglottone 1 - Wong, Darren C. J.; Amarasinghe, Ranamalie; Rodriguez-Delgado, Claudia; Eyles, Rodney; Pichersky, Eran; Peakall, Rod (Frontiers in Plant Science, 2017)
The Australian sexually deceptive orchid, Chiloglottis trapeziformis employs a unique UV-B-dependent floral volatile, chiloglottone 1 for specific male wasp pollinator attraction. Chiloglottone 1 and related variants (2,5-dialkylcyclohexane-1,3-diones), represent a unique class of specialized metabolites presumed to be the product of cyclization between two fatty acid (FA) precursors. However, the genes involved in the biosynthesis of precursors, intermediates, and transcriptional regulation remains to be discovered. Chiloglottone 1 production occurs in the aggregation of calli (callus) on the labellum under continuous UV-B light. Therefore, deep sequencing, transcriptome assembly, and differential expression analysis were performed across different tissue types and UV-B treatments. Transcripts expressed in the callus and labellum (~ 23,000 transcripts) were highly specialized and enriched for a diversity of known and novel metabolic pathways. Differential expression analysis between chiloglottone-emitting callus versus the remainder of the labellum showed strong coordinated induction of entire FA biosynthesis and β-oxidation pathways including genes encoding Ketoacyl-ACP Synthase, Acyl-CoA Oxidase, and Multifunctional Protein. Phylogenetic analysis revealed potential gene duplicates with tissue-specific differential regulation including two Acyl-ACP Thioesterase B and a Ketoacyl-ACP Synthase genes. UV-B treatment induced the activation of UVR8-mediated signaling and large-scale transcriptome changes in both tissues, however, neither FA biosynthesis/β-oxidation nor other lipid metabolic pathways showed clear indications of concerted differential expression. Gene co-expression network analysis identified three callus-specific modules enriched with various lipid metabolism categories. These networks also highlight promising candidates involved in the cyclization of chiloglottone 1 intermediates (e.g. Bet v I and dimeric α,β barrel proteins) and orchestrating regulation of precursor pathways (e.g. AP2/ERF) given a strong co-regulation with FA biosynthesis/β-oxidation genes. Possible alternative biosynthetic routes for precursors (e.g. aldehyde dehydrogenases) were also indicated. Our comprehensive study constitute the first step towards understanding the biosynthetic pathways involved in chiloglottone 1 production in Chiloglottis trapeziformis – supporting the roles of FA metabolism in planta, gene duplication as a potential source of new genes, and co-regulation of novel pathway genes in a tissue-specific manner. This study also provides a new and valuable resource for future discovery and comparative studies in plant specialized metabolism of other orchids and non-model plants.